Lifetime trauma, mental well-being, alcohol and help-seeking; the phenomenological experience of veterans residing in Northern Ireland - Catherine Hitch; Paul Toner; Hannah Champion; Cherie Armour (BMC Psychology, 2024)
Abstract Background Veteran residents in Northern Ireland (NI) are an under-researched population. Little is known about their experiences of trauma and mental health management. The overall mental well-being of veterans living in NI may be poorer than other veteran populations, due to the challenges presented by the unique landscape. Understanding their experiences is crucial for providing appropriate, targeted support. Method Six male veterans, who had received a mental health diagnosis, living in NI and all aged > 40 years participated. Semi-structured interviews, using open-ended questions, were conducted over the telephone. Interpretative phenomenological analysis was used to explore their experiences. Results Two experiential themes were identified each containing three experiential statements. Statements for ‘an extreme lack of’ included: lack of mental health literacy/awareness; lack of expectations of official support; lack of a sense of perceived appreciation. Statements for ‘an extreme abundance of’ included: exacerbated exposure to a range of extreme environments; high levels of ruled-based living; high levels of engaging with informal/local level support. Conclusions Several experiential statements aligned with existing literature, including having poor mental health literacy and problem recognition, and heavily utilising social support versus formal help-seeking. Some novel findings included bouncing between extreme positive and negative environments which could be as detrimental to mental health as experiencing conflict trauma. Heavy alcohol use was just another rule soldiers followed. Positive help-seeking experiences failed to improve poor opinions of support organisations. Finally, poor self-perceptions connected to military status are pertinent in NI, which seems to fuel self-marginalisation and distrust. A combination of factors likely contributes to many veterans living in NI having poorer mental well-being. Novel findings would benefit from further exploration as understanding how NI veterans interpret their experiences is key to providing adequate healthcare.